The Influence Of Source Credibility And Discount Framing On Brand Reputation And Brand Image In Increasing Buying Interest In E-Commerce Shopee Indonesia - Muhammad Iqbal Prawira Yuda; Albari (Cita konsultindo, 2025)
This study aims to analyze the influence of source credibility, discount framing, brand reputation, and brand image on purchase intention among consumers of the Shopee Indonesia e-commerce platform. The research involved 200 respondents who have purchase intentions toward products sold on Shopee and employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that source credibility and discount framing significantly affect brand image, while discount framing also exerts a strong influence on brand reputation. Furthermore, brand reputation positively enhances brand image, and brand image emerges as the most dominant factor driving purchase intention, followed by brand reputation. These results indicate that marketing strategies emphasizing influencer credibility, transparent discount communication, and the strengthening of brand image and brand reputation are essential for increasing consumer purchase intention.